PENGARUH MATHEMATICS PHOBIA, ADVERSITY QUOTIENT, LOCUS OF CONTROL TERHADAP LITERASI MATEMATIKA PADA SISWA SEKOLAH MENENGAH - Muhammad Yogi Ramadhan; Saleh Haji; Hari Sumardi (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
This study aims to analyze the effect of math phobia, locus of control, and adversity quotient on the mathematical literacy skills of junior high school students. This type of research is ex post facto research in the form of correlation. The population in this study were all class VII students of SMPQ Darul Maarif and SMP IT Hidayatul Falah Rejang Lebong. The sampling technique used random simple sampling in which 47 students were selected at SMPQ Darul Maarif and 50 students at SMP IT Hidayatul Falah Rejang Lebong. The collection was carried out using a mathematics phobia, locus of control, and adversity quotient questionnaire and test sheets for students' mathematical literacy abilities. Research data were analyzed using path analysis techniques (path analysis). Research shows that there is a significant positive effect both simultaneously and partially between math phobia, locus of control, and adversity quotient on mathematical literacy skills